THE QUALITY OF INCLUSIVE EDUCATION SERVICES FOR CHILDREN WITH SPECIAL NEEDS (CSN) IN INCLUSIVE SCHOOLS IN PALU CITY - Sintia Dewi Mateka; Syahruddin Khattab; Suasa Suasa; Sasterio Sasterio (Program Studi PGSD Universitas Flores, 2025)
This study aims to analyze the quality of inclusive education services for Children with Special Needs (CSN) in Palu City using the New Public Service (NPS) approach developed by Robert B. Denhardt. The NPS framework emphasizes a public service orientation that does not merely focus on efficiency or customer satisfaction, but rather positions citizens as active participants in decision-making processes. It also underscores the importance of democratic values, ethics, accountability, and collaboration. This study employs a qualitative method, with data collected through in-depth interviews, observations, and document analysis conducted in several inclusive schools in Palu. The findings indicate that the quality of education services for CSN continues to face a number of challenges, including limited community involvement, insufficient budgetary and infrastructural support, and weak coordination among schools, families, and other stakeholders. Although the principle of inclusivity has been formally adopted, its implementation remains far from the core tenets of NPS. Therefore, strengthening participatory governance that is responsive to the needs of CSN is essential to realizing an inclusive and equitable education service.